(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article examines Russian folklore and discusses methodological issues on this material: traditional folklore studies, a new interpretation of traditional material and new studies of modern verbal art. The study of oral folk art is shifting to clarifying the specifics of other genres of Russian folk poetry, and the related topic of authenticity, to research in the field of urban folklore, problems of personal narrative and oral history, modern folklore.